Preliminary study of sago fine waste as a sand replacement material for cement brick - Izaan, I Hadi; Hani, A. Suraya; A. W., Norhayati; O., Mohamad Hairi; J., Zalipah; A. H., Noor Azlina; S., Norhafizah; Mia Wimala, Mia Wimala (2022)
This paper presented a preliminary results of utilization sago fine waste as a sand replacement material for cement bricks. Sago waste is a by-product of the extraction of sago starch. Usually, the bark is not utilized for other products and being dumped directly into the rivers or left for natural degradation. About 32,250 tons of sago bark waste annually. Sand however usually obtained by using machinery at the riverbank which greatly contribute to damaging the ecosystem of the river and contributing to global warming. For environmental protection and sustainable development, extensive research has been conducted on the production of bricks from waste materials. The replacement percentage of SFW are 0%, 5%, 10%, 15%, 20% and 25% with water content of 50% and 60%. Density, water absorption and compressive strength are the properties that have been investigated. From the results obtained, both density and compressive strength are decreasing as the percentages of SFW increasing. On the other hand, from the data of water absorption it was found that the percentage of water absorption of brick was increased correspond to the increasing percentages of the SFW. Based on the findings, the optimum brick properties are SFW1W0.6 with the strength 5.18 MPa that can be used as non-load bearing bricks and the optimum percentage of water absorption is at 13.33%. From this study, it was found that the replacement of sand by SFW give a significant impact on density, strength, and water absorption performance of concrete brick.